2013
DOI: 10.5455/vetworld.2013.151-155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding processed sweet sorghum (Sorghum bicolour (L) moench) crushed residue based complete ration on growth performance and feeding behavior of murrah buffalo calves

Abstract: How to cite this article: Seshaiah CV, Rao SJ, Reddy YR, Nagalakshmi D, Mahender M and Harikrishna C (2013) Effect of feeding processed sweet sorghum (Sorghum bicolour (L) moench) crushed residue based complete ration on growth performance and feeding behavior of murrah buffalo calves, Vet World 6(3): 151-155, doi:10.5455/vetworld.2013.151-155 Introduction digestibility of nutrients. Now a day's expanders are being used in feed industry as an alternative for Sweet sorghum (Sorghum bicolour (L) moench), pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…No significant difference was found among the three rations in the digestibility coefficient of DM, OM, CP, EE, CF, NFE, NDF and ADF. Our results were in consistent with the findings of Seshaiah and Ramana Reddy [22] who observed no difference (p>0.05) in the digestibility coefficient of DM, OM, CP, EE, CF, NFE, NDF and ADF in graded Murrah calves by replacing the conventional roughage source (sorghum stover) with unconventional roughage source (sweet sorghum stover bagasse) which were value bearing different superscripts in a row differ significantly (P<0.05), D1, D2, D3 refers to complete rations of sorghum stover (D1), maize stover (D2) and sweet sorghum stover (D3) with roughage to concentrate ratio 60:40 respectively. SEM=Standard error of the mean, DMI=Dry matter intake, DCP=Digestible crude protein, TDN=Total digestible nutrients, DE=Digestible energy, ME=Metabolizable energy, DM=Dry matter, OM=Organic matter, EE=Ether extract, CF=Crude fibre, NFE=Nitrogen free extract, NDF=Neutral detergent fibre, ADF=Acid detergent fibre, CP=Crude protein [24] stated that the grinding and blending of crop residues with concentrate (in a given ratio) into mash was found to be useful for efficient utilisation of crop residues in ruminants.…”
Section: Nutrient Digestibilitysupporting
confidence: 93%
See 1 more Smart Citation
“…No significant difference was found among the three rations in the digestibility coefficient of DM, OM, CP, EE, CF, NFE, NDF and ADF. Our results were in consistent with the findings of Seshaiah and Ramana Reddy [22] who observed no difference (p>0.05) in the digestibility coefficient of DM, OM, CP, EE, CF, NFE, NDF and ADF in graded Murrah calves by replacing the conventional roughage source (sorghum stover) with unconventional roughage source (sweet sorghum stover bagasse) which were value bearing different superscripts in a row differ significantly (P<0.05), D1, D2, D3 refers to complete rations of sorghum stover (D1), maize stover (D2) and sweet sorghum stover (D3) with roughage to concentrate ratio 60:40 respectively. SEM=Standard error of the mean, DMI=Dry matter intake, DCP=Digestible crude protein, TDN=Total digestible nutrients, DE=Digestible energy, ME=Metabolizable energy, DM=Dry matter, OM=Organic matter, EE=Ether extract, CF=Crude fibre, NFE=Nitrogen free extract, NDF=Neutral detergent fibre, ADF=Acid detergent fibre, CP=Crude protein [24] stated that the grinding and blending of crop residues with concentrate (in a given ratio) into mash was found to be useful for efficient utilisation of crop residues in ruminants.…”
Section: Nutrient Digestibilitysupporting
confidence: 93%
“…The similar DMI observed with the experimental ration containing D3 in the present study indicated that the sweet sorghum stover was equally palatable in comparison with the rations containing sorghum stover and maize stover. The results obtained were in agreement with Seshaiah and Ramana Reddy [22], who found that the DMI/kg metabolic body weight was similar in lactating graded Murrah buffaloes fed sweet sorghum bagasse mash diet with sorghum stover mash diet. Similar results were found by Jadhav and Deshmukh [23] on two complete rations containing 60% level of black gram straw and wheat straw in sheep.…”
Section: Voluntary Feed Intakesupporting
confidence: 91%
“…Complete feeding system is considered better over separate feeding system [ 60 ]. Complete ration has beneficial effects in terms of utilization of low-grade roughages; besides, its densification into feed blocks [ 19 , 26 , 61 ] or extrusion of the complete mash feed into pellets [ 7 , 8 , 12 , 14 , 17 , 27 , 62 ] distinctly improves the DM/nutrient intake and nutritive value of mash diet, thereby ensures efficient utilization of the feed [ 63 ]. A higher intake, therefore, gives scope for using cheap ingredient and various bulky by-products that are available locally to economize livestock feeding.…”
Section: Feeding Complete Feedmentioning
confidence: 99%
“…Another processing method for feeding complete diets is expansion-extrusion which also has proved to be better than feeding complete diet in mash or conventional forms. To identify the appropriate processing method for efficient utilization of SSB after blending with concentrate in complete diets for buffalo calves [ 14 , 17 ] and growing lambs [ 18 ], expander-extruded pellet complete diets were observed to be better in terms of nutrient utilization efficiency and microbial N supply than chopped or mash forms of the complete diets. The complete diet based on paddy straw incorporated at 50% level was more palatable to sheep when it was expander-extruder pelleted and such processing improved the nutritive value of the diet [ 70 ].…”
Section: Feeding Complete Feedmentioning
confidence: 99%
See 1 more Smart Citation